A comparative study of serum adiponectin levels in patients of acute coronary syndrome with and without central obesity - Tiwari, Shashank R.; S., Lokesh; P., Arunprasath; R., Arun Kumar (International Journal of Advances in Medicine, 2019)
Background: Coronary artery disease burden has been on a rise globally with it emerging as the principle cause of death even in the Indian subcontinent. Serum adiponectin has recently gained interest due to its close relation with atherosclerotic CAD and Metabolic syndrome. The levels of serum adiponectin are reduced in ACS. There is a paucity of studies in South Indian population comparing the effect of central obesity in patient with ACS. The aim of the present endeavour was to study the association of serum adiponectin in risk evaluation of patient with acute coronary syndrome with and without central obesity Methods: The study was conducted in a tertiary center in patient who presented with first time ACS they were grouped into two groups based on the presence and absence of central obesity. Central obesity was defined on the basis of waist to hip ratio. Serum adiponectin levels were estimated in both the groups using ELISA method. The results were statistically analyzed using t- test. Results: Authors concluded that the mean age of patients presenting first time with ACS was 55±12years in both the group. There was a significantly raised LDL and Total Cholesterol (TC) level in patient with central obesity. The estimated serum adiponectin level was reduced in both the group with more significant reduction in group with central obesity. The mean adiponectin level in CAD patients with central obesity was 2.326±1.437µg/ml as compared to 3.486±1.6999μg/ml in patients without central obesity, which was statistically significant (p value <0.0049). Conclusions: Authors concluded that serum adiponectin levels were reduced in both the group with ACS with a further reduction in patient with central obesity. It was also observed that there was a significant relation between adiponectin level and visceral fat as compared to superficial fat, as adiponectin was significantly reduced in patient higher waist-hip ratio.